IMPLEMENTASI TEKNOLOGI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS X DI SMA NEGERI 1 SIOMPU KABUPATEN BUTON SELATAN - Raju; La Jusu; Darmayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of information and communication technology has brought significant changes to the field of education, including Islamic Religious Education (PAI). This study aims to examine the effectiveness of technology implementation in Grade X PAI learning at SMA Negeri 1 Siompu, South Buton Regency, specifically in terms of material understanding, learning motivation, and student independence, as well as to analyze teacher readiness and student responses to technology-based learning. The research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with PAI teachers and Grade X students, and documentation. Data analysis used the Miles, Huberman, and Saldana model through data condensation, data presentation, and conclusion drawing stages. Data validity was tested through source triangulation, method triangulation, and member checking. The findings reveal that the implementation of digital technologies such as Google Classroom, WhatsApp, and Google Meet effectively increased students' material understanding by 20-30%, significantly enhanced learning motivation, and rapidly developed student independence despite the school facing infrastructure limitations including limited electricity access and unstable internet networks. Teachers demonstrated good readiness through creativity in overcoming technical barriers with hybrid learning strategies and offline material provision. Students responded very positively with high enthusiasm and active participation in learning. This research contributes to achieving SDGs goal 4 on quality education and goal 10 on reducing inequalities by proving that technology can serve as a means of equalizing access to quality education in remote areas.